Electronic Communication of Entrepreneurs during the Covid-19 Pandemic in the Czech Republic - Sobotovičová, Sárka; Blechová, Beáta; Pražák, Tomáš (Journal of Telecommunications and the Digital Economy, 2023)
The aim of this article is to find out the attitudes of business entities towards the helpfulness and frequency of the use of electronic communication with government administration institutions in the Czech Republic during the Covid-19 pandemic. The research was conducted in the form of a questionnaire survey of 464 respondents. Based on the primary research, the change in the use of electronic communication was verified. The most important factors influencing satisfaction in communication are functionality, speed and delivery confirmation. The increased need for electronic communication was found especially in micro and small enterprises and in the services sector.